Alveolar Macrophages Are Key Players in the Modulation of the Respiratory Antiviral Immunity Induced by Orally Administered Lacticaseibacillus rhamnosus CRL1505 - Garcia-Castillo, Valeria; Tomokiyo, Mikado; Raya Tonetti, Fernanda; Islam, Md. Aminul; Takahashi, Hideki; Kitazawa, Haruki; Villena, Julio (Frontiers in Immunology, 2020)
The oral administration of Lacticaseibacillus rhamnosus CRL1505 differentially modulates the respiratory innate antiviral immune response triggered by Toll-like receptor 3 (TLR3) activation in infant mice, improving the resistance to Respiratory Syncytial Virus (RSV) infection. In this work, by using macrophages depletion experiments and a detailed study of their production of cytokines and antiviral factors we clearly demonstrated the key role of this immune cell population in the improvement of both viral elimination and the protection against lung tissue damage induced by the CRL1505 strain. Orally administered L. rhamnosus CRL1505 activated alveolar macrophages and enhanced their ability to produce type I interferons (IFNs) and IFN-γ in response to RSV infection. Moreover, an increased expression of IFNAR1, Mx2, OAS1, OAS2, RNAseL, and IFITM3 was observed in alveolar macrophages after the oral treatment with L. rhamnosus CRL1505, which was consistent with the enhanced RSV clearance. The depletion of alveolar macrophages by the time of L. rhamnosus CRL1505 administration abolished the ability of infant mice to produce increased levels of IL-10 in response to RSV infection. However, no improvement in IL-10 production was observed when primary cultures of alveolar macrophages obtained from CRL1505-treated mice were analyzed. Of note, alveolar macrophages from the CRL1505 group had an increased production of IL-6 and IL-27 suggesting that these cells may play an important role in limiting inflammation and protecting lung function during RSV infection, by increasing the maturation and activation of Treg cells and their subsequent production of IL-10. In addition, we provided evidence of the important role of CD4+ cells and IFN-γ in the activation of alveolar macrophages highlighting a putative pathway through which the intestinal and respiratory mucosa are communicated under the influence of L. rhamnosus CRL1505.